Faʿāliyyat Namūdzaj Farīq al-Alʿāb al-Buthūlah (Teams Games Tournament) fī Māddah ʿAwāmil an-Nawāshib li-Fiʿl al-Mudhāriʿ fī al-Madrasah al-Islāmiyyah al-Mutakāmilah Mīdān - Sekar Wulandari; Fatma Yulia (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
Some students consider Arabic a frightening subject. The word 'difficult' is the main term used in their responses when asked about the reason. As a result, this leads to a lack of interest among students in learning Arabic. Therefore, a model is necessary that can attract students' interest during the learning process. This research aims to determine the use and effectiveness of the Teams Games Tournament learning model in the subject of present tense accusatives for eighth grade students at Al-Ulum Islamic Junior High School Integrated of Medan. The researcher employs a mixed-method approach, incorporating qualitative methods such as observation, interviews, and documentation, alongside quantitative data collected through a Likert scale questionnaire, which is analyzed using a percentage-based formula. The researcher found that this model has a significant positive impact on students desire to learn Arabic, especially in the subject of the factors causing the accusative case for the present tense verb, reaching a percentage of 81.6% in the category 'very effective'. These results were supported by the interview that students feel more enjoyable, motivated, and easier to understand this material and contribute to cooperation in the group and increase their concentration. This research is an alternative and a solution for teachers, especially Arabic language teachers, who face the issue of students lack of desire and low concentration when learning.Key words: Effectiveness, Teams Games Tournament, Present Tense Accusatives